The distribution law and coupling factors of debris flows in the G318 Linzhi–Lhasa section of the Sichuan–Tibet traffic corridor - He, Na; Song, Yabing; Hu, Guisheng; Yang, Zhiquan; Fu, Qixuan; Gurkalo, Filip (Frontiers in Ecology and Evolution, 2023)
In recent years, debris flow disasters have occurred frequently along the highway, causing river blockages and road interruptions, which seriously threaten the safety of people's lives and property. Highway G318 is an important throat project linking Sichuan and Tibet; at the same time, it is an important channel for the economic development of Sichuan and Tibet and the transportation of national defense materials. Taking the Linzhi–Lhasa Section of Highway G318 as an example, this study analyses the distribution law and characteristics of coupling factors of debris flows in the study area (under its topographical, hydrometeorological, geological, and structural conditions) using remote sensing interpretation, field surveys, and mathematical statistics. The research shows that: (1) The types and quantity of debris flows in the region show statistical laws under the factors of the slope, slope aspect, drainage area, and gradient of the gully. The vegetation coverage in the upper reaches of the Nyang River valley gradually decreases, and the average debris flow disaster density is 0.529/km, which is the most densely distributed area of debris flow. (2) The distribution density of regional debris flows in narrow valleys is greater than that in wide valleys, and those in the Nyang River basin are greater than those in the Lhasa River basin. (3) By comparing the tectonic geological map and the debris flow distribution map, it was found that the debris flow distribution is controlled by faults, and 71% of the debris flow basins have faults. (4) There is a significant positive correlation between the gradient of the material source area and the gradient of the debris flow gully, as well as a close positive correlation between the rainfall and the fault density, and a close negative correlation between the average gradient and the drainage area. Due to the unique topography and geomorphology of different regions, a difference in meteorology and hydrology occurred. This further affected the topography, geomorphology, and distribution of debris flow disasters. Based on the study of the distribution law of regional debris flow and geological environmental factors, this study provides strong support for regional debris flow prevention and related research.